Scaling behavior of dynamic hysteresis in hard PZT bulk ceramics under influence of compressive stress - Wongdamnern N. (2014)
Effects of electric field-amplitude and mechanical stress on hysteresis area were investigated in partially depoled hard PZT bulk ceramic. At any compressive stress, the hysteresis area was found to depend on the field-amplitude with a same set of exponents to the power-law scaling. Consequently, inclusion of compressive stresses into the power-law was also obtained in the form of < A - Aσ=0 > α E 05.1 σ1.19 which indicated the difference of the energy dissipation between the under-stress and stress-free conditions. © 2008 Trans Tech Publications, Switzerland.